PENGARUH LABELISASI HALAL DAN HARGA TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK MINUMAN ICE CREAM & TEA MIXUE DI KOTA SIDOARJO - Damayanti, Salsabila Putri; Dewi Riza Lisvi Vahlevi (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2025)
To determine how the pricing and halal labeling of Ice Cream & Tea Mixue drinks, one of the new items imported into Indonesia since 2020, affect the decision-making of the country's mostly Muslim citizens on the halal content of the products they eat. The purpose of this study is to ascertain how pricing and halal labelling affect consumers' choices to buy Ice Cream & Tea Mixue beverage goods at the same time. This study employs quantitative procedures, which are ways of doing research that utilize test apparatus to generate quantitative data—primary data—obtained using statistical computation tools. The samples used in this survey were taken over a period of ten days from fifty participants. Every inquiry is assessed using a Likert scale. By requesting friends to serve as samples, the sampling approach employs probability snowball sampling, which starts with a tiny sample and keeps going until the number of samples rises. The Statistical Package for the Social Sciences (SPSS) version 26 was used to compute the multiple linear regression techniques, reliability tests, validation tests, determination tests, T tests, and F tests that were used to assess the data that was gathered using Google Form. The findings of this study demonstrated that, with a significance value of 0.003, which is less than 0.05, The Halal label has a positive and significant influence on the purchase decision variable for Ice Cream & Tea Mixue beverage goods. Because the price variable of 0.000 is less than 0.05, it has a substantial and favorable impact on consumers' choices to buy Ice Cream & Tea Mixue beverage goods. Price and halal labeling have a big impact on consumers' choices to buy ice cream and tea mixue drinks, both concurrently and in part.